An introduction to research @ UiTM Perak version 1.0 / Asmalia Che Ahmad ... [et al.] - Che Ahmad, Asmalia; Ibrahim, Nur Hisham; Abdul Tharim, Asniza Hamimi; Ahmad Radzi, Mohamad Quzami An-Nuur; Mohamed Saraf, Mohamad Haizam; Ahmad, Nursaadatun Nisak (Universiti Teknologi MARA, Perak, 2020)
Research @ UiTM Perak v1.0 is an organized collection research database using an online cloud application at UiTM Perak. This online cloud application is being stored and accessed electronically from any computer. This research database application interacts with university administration as well as researchers to capture and analyze research data. This application uses Google site as a base platform. The objective of this research database application is to administer the grant application of researcher from UiTM Perak. Information on lead researchers, the research members, research title and research summary are collected in order to manage and monitor grants application's effort among researchers at UiTM Perak. This research database application was developed by considering the user-friendly and online cloud base platform that is accessible to all UiTM researchers. It can be easily accessed using multiple devices such as smartphone, tablet and computer. From this research database application, the research administrator could summarize the research grant application using Google cloud platform. The novelty of this research database application is on the management and monitoring of grant applications. Finally, this online cloud application may produce the success rates of grant winners for research strategic planning in the future.